Empirical Determinants and Patterns of Research and Development Investment in Asia - Margarita Debuque-Gonzales (Asian Development Bank (ADB), 2013)
This paper investigates the financial determinants of research and development (R&D) investment in Asia, where innovation is naturally seen as the key driver of future (high) economic growth. We sample listed nonfinancial firms from eight economies in region (the People's Republic of China; Hong Kong, China; India; Indonesia; the Republic of Korea; Malaysia; the Philippines; and Singapore) for the period 2002–2011 using the Oriana database. Panel data regressions show sensitivity of R&D investment to changes in cash flow, indicating reliance on internal financing of R&D and financially constrained firms, and a greater role of debt, rather than equity, as a source of external financing. In terms of alternative uses of funds, dividend payments by firms seem to divert from their spending on R&D, but investments in financial assets do not. In terms of ownership structure, empirical results show that both higher domestic ownership concentration and higher foreign ownership tend to lower cash flow sensitivity of R&D investment, suggesting more stable funding of innovation. Overall, there does not seem to be an extreme preference of firm shareholders for short-term returns at the expense of long-term productivity. However, there is clearly a gain for firms as well as economies they are in with better access to external financing of R&D.
hdl:11540/2306
Keywords: D92; G30; O30; O40; 330; R&D investment; financing innovation; cash flow; R&D financing constraints; Asia